Theory of environmental sex determination: Trending populations in stressful environments. (16th February 2021) - Crowley, Philip H.; Labonne, Jacques
Abstract: Species that have sex determined by environmental conditions during development (i.e., environmental sex determination [ESD]) are especially vulnerable to environmental change, including altered stress levels, habitat loss, and species translocations. These factors can produce multigenerational trends in population size and eco‐evolutionary dynamics not captured by existing theory based on lifetime reproductive success ( R 0 ). Here, we extend ESD theory to use per capita growth rate r as a more appropriate measure of evolutionary success (fitness), and we demonstrate the importance of this change when males and females can differ in maturation times and when maturation times vary with local conditions (plasticity). In these cases, we show that primary and secondary sex ratios may be strongly biased; that optimal maturation times, when locally plastic, depend on the balance between mortality and growth effects; and that plasticity of maturation times can ameliorate fitness costs of increasing environmental stress.